Towards a Model of Third-Party Liability for Wage Theft: Lessons from Other Regulatory Regimes - Mildren, Kellie (Canadian Labour and Employment Law Journal, 2017)
Given the growing trend towards "fissured" employment structures char- acterized by the use of subcontractors and supply chains, the lack of any mech- anism for imposing third-party liability is a serious gap in employment standards legislation. By limiting liability to the direct employer, traditionally conceived, the legislation as it has been interpreted can leave victims of wage theft without recourse against a judgment-proof subcontractor. This paper seeks to address that deficiency by focusing on Ontario's successful experience with various statutory regimes that provide for third-party liability, including construction liens and trusts, the internal responsibility system under occupational health and safety legislation, and "cause or permit" regulatory liability in environmental and other public welfare legislation. Building on the key principles of these schemes, all of which create non-delegable responsibilities in the face of arm's- length subcontracted relationships, the author proposes the adoption of a system of joint and several liability for entities that "cause or permit" violations of employment standards. This would require lead companies to take some of the responsibility for compliance by subcontractors down the supply chain, thereby providing vulnerable workers with stronger protections against non-payment of wages. At the same time, the author argues, this approach would strike an appropriate balance with the needs of employers, because a number of low-cost tools would be available to lead companies to spread risk, and third-party lia- bility would not capture subcontracting arrangements that do not jeopardize the wage entitlements of vulnerable workers.